Impact of climate change on the potato crop and biodiversity in its center of origin - Quiróz, R.; Ramírez, D.; Kroschel, Jürgen; Andrade-Piedra, J.L.; Barreda, C.; Condori, B.; Mares, V.; Monneveux, P.; Pérez, W. (Walter de Gruyter GmbH, 2018)
The Andean region is the most important center of potato diversity in the world. The global warming trend which has taken place since the 1950s, that is 2-3 times the reported global warming and the continuous presence of extreme events makes this region a live laboratory to study the impact of climate change. In this review, we first present the current knowledge on climate change in the Andes, as compared to changes in other mountain areas, and the globe in general. Then, the review describes the ecophysiological strategies to cope and adapt to changes in atmospheric CO2 levels, temperature and soil water availability. As climate change also has a significant effect on the magnitude and frequency of the incidence of pests and diseases, the current knowledge of the dynamics of vectors in the Andean region is discussed. The use of modeling techniques to describe changes in the range expansion and number of insect pest generations per year as affected by increases in temperature is also presented. Finally, the review deals with the use of crop modeling to analyze the likely impact of projected climate scenarios on potato yield and tuber initiation.